The media paradox: influence on human shark perceptions and potential conservation impacts - Ostrovski, Raquel Lubambo; Violante, Guilherme Martins; de Brito, Mariana Reis; Valentin, Jean Louis; Vianna, Marcelo (Ethnobiology and Conservation, 2021)
Sharks, due to some of their characteristics such as prominent teeth and size, cause fear in many people. This feeling can be evidenced due to encounters with these animals or sustained by media information. Currently, negative information on these animals, present in movies and the news, for example, has contributed to a worldwide feeling of "fear" or "anger" towards sharks in the general public. On the other hand, efforts to better understand these animals have increased. In addition to films and documentaries, many scientific and environmental education groups have attempted to improve or alleviate, public perception concerning this significant fear and promote shark conservation. In this context, we analyzed the perceptions of 354 people living in Rio de Janeiro, a coastal city in southeastern Brazil, by applying a structured online questionnaire about sharks. The findings reported herein indicate direct media influence on respondent perceptions, according to the “good” or “bad” image that media vehicles pass on concerning these animals, and that, despite an established fear of sharks, public support for their conservation is maintained. The factor analysis indicated a relationship between older people and more fear, and less fear among people aged 20-40 years. We believe that the lesser fear in the latter is related to the influence of the current media in this age group, such as documentaries and social networks, while older respondents lived in a period with less environmental information and became more susceptible to shark negative films and media, in which the fear persists today.